Serbs in the works of Demetrios Cydones - Pavlović Bojana (Zbornik Radova Vizantološkog Instituta, 2012)
One of the main topics of the works of Cydones is the foreign policy of Byzantium. Mutual incomprehension of Byzantium and the West, the growing threat and fear of the Ottoman Turks, lack of trust and, in a way, animosity towards the neighboring countries (primarily towards Bulgaria and Serbia in the time of Stefan Dušan and his immediate successors), represent three most important factors of that foreign policy in which Cydones also took part. This article deals with Cydones’ perception of Serbs and the information he provides on them in his works. Two major parts can be discerned in this paper. The first chapters deal with the information Cydones’ provides on Serbs in his letters. The last chapter, in which his speeches and the preambule of the charter of John V Palaiologos written by Cydones are being analyzed, deals with his perception of the Byzantine Slavic neighbor.